Starch biosynthesis and crop bioengineering - Andreas Blennow; Kim Henrik Hebelstup; Bent Larsen Petersen (Grain & Oil Science and Technology)
Starch is an essential commodity for humans and other animals. Future demands require qualitative and quantitative improvement by crop and post-harvest engineering that calls for comprehensive actions requiring increased fundamental knowledge on starch biosynthesis, development of advanced breeding strategies, efficient farming, and well-adapted and up scalable extraction protocols for diverse starch products. Recent staggering progress in molecular breeding techniques, especially genome editing, have enabled generation of higher starch yield and special functional qualities required to support such advancement. However, this necessitates fundamental biochemical and mechanistic understanding of starch biosynthesis and the variegated starch crop germplasms, all of which are closely linked to the relationships between starch molecular structures and functionality of various starch types as directed by the different capabilities of starch crop genotypes. We here review starch biosynthesis and its genetic foundation with a focus on increasing nutritional and health-promoting value of starch especially through bioengineering of the high amylose trait.